Interest Groups and U.S. Foreign Policy towards Cuba: the Restoration of Capitalism in Cuba and the Changing Interest Group Politics - Koçak, Canberk (2017)
The Cuban-American lobby successfully influenced Congress and various presidential administrations from the early 1980s until nearly the end of the century on U.S. foreign policy towards Cuba. Although two major events, the passage of the Trade Sanction Reform and Export Enhancement Act of 2000, and the Elián González affair of the same year, dramatically reduced the power of this conservative ethnic interest group, its influence continued during the George W. Bush presidency. Despite the lobby’s active role, since 2008 the opposition of several political actors towards the sanctions regime, such as the agribusiness lobby, the administration of Barack Obama, and a significant number of Congressmen from both major parties, created an environment of major competition between two camps with distinct policy agendas. With the focus on the parallelism between the economic reforms on the island, and the changing American interest group politics, this paper seeks to study the determinants of the embargoes continuity in the 21st century, and the conditions that shape the new policy announced by the Obama administration in late 2014.